Peningkatan Kondisi Fisik Melalui Pengenalan Sport Nutrition Kepada Atlet dan Pelatih Kabupaten Sumenep - Nugroho Agung Supriyanto; Abdul Azis; Andi Fepriyanto; Ainur Rasyid; Dian Helaprahara (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2022)
One type of sport is performance sports. Achievement can be achieved by several factors. One of them is the nutritional factor. Nutrition is one of the vital and important components to improve the athlete's condition in order to achieve performance maximum and achievement. Nutrition for each sport varies depending on the type of energy used. In Sumenep Regency, athletes and coaches are still confused about sport nutrition and they also don't have experts in the field of sports. Especially in Sumenep regency has a lot of potential for athletes. The aim of this service is to introduce the importance of sport nutrition in improving the condition of athletes. The method used is the teaching method with power point. The result of this introduction is that athletes and coaches understand about nutrition to be able to increase performance levels so that they can achieve maximum performance.